The use of AI in sales funnel management in international companies - Vauhkonen, Iida (My University, 2025)
During the past few years artificial intelligence (AI) has become a focal point of academic discourse and research. The possibilities of using AI as a tool in enhancing various business processes is considered a wideranging trend in the globalized business world. The amount of companies using AI in their business operations has in fact doubled during the recent years which can be explained with the variety of AI technologies available that can be curated to meet individual companies’ unique needs. The question that many companies face is how they can profit most from using AI. The aim of this thesis is to examine the use of AI in sales funnel management in international companies. The sources, results and findings of this thesis are based on academic literature provided by the University of Turku. This thesis commences with an overview of the most recent developments and trends in the international business environment including the breakthrough of AI. The theory section of this thesis begins with examining the sales funnel framework that is widely acknowledged and used in structuring companies’ customer acquisition activities. In order to foster a deeper understanding of the phenomenon the customer journey framework is presented together with the sales funnel. The customer journey analysis brings insights from the customer’s perspective of the purchasing journey whereas sales funnel pictures the company’s view. Together the two frameworks explain the customer’s purchasing journey from the initial awareness to purchase and beyond. The stages of the sales funnel are presented in detail in order to point out the possible stages where AI can make difference. The findings of this thesis demonstrate the transforming power of AI in sales and marketing related tasks. Emphasizing that the use of AI is most efficient in repeatable, routine and standard tasks. Regarding customer acquisition inside sales funnels the most pivotal points are prospecting and conversion. The findings of this thesis underline the possibilities of AI in lead prospecting and lead conversion. In these points of the sales funnel AI can significantly decrease the workload of sales organizations. For instance, data analysis, machine learning and personalisation can be used to make lead prospecting more efficient. Many sales tasks still require human intelligence which is why AI is often used as a human intelligence augmentation tool. Despite the numerous advantages of artificial intelligence, the need for human intelligence is inevitable. The findings of this thesis highlight that the disparities in companies and countries finances and other resources have a huge impact on the scale that AI is adopted in a company’s operations. When a company operates internationally the amount of prospect customers increases and diversifies which is why companies need efficient sales and marketing processes and therefore well-functioning sales funnels.

Viime vuosien aikana tekoäly on noussut keskeiseksi akateemisen keskustelun ja tutkimuksen kohteeksi. Yleinen trendi kansainvälisessä liiketoimintaympäristössä on ollut tarkastella tekoälyn tarjoamia mahdollisuuksia liiketoiminnan tehostamiseen. Tekoälyä hyödyntävien yritysten määrä onkin lähes tuplaantunut viime vuosien aikana, mikä selittyy osittain sillä, että tekoälyn mahdollistamien teknologioiden määrä on kasvussa ja niitä voidaan räätälöidä yksittäisten yritysten tarpeisiin. Keskeisintä yrityksille on kuitenkin ymmärtää, miten tekoälyä voidaan hyödyntää tehokkaasti. Tämän tutkielman tarkoitus on tutkia tekoälyn käyttöä myyntisuppilon hallinnassa kansainvälisissä yrityksissä. Tutkielman lähteet, tulokset ja havainnot perustuvat pitkälti Turun Yliopiston tarjoamaan akateemiseen kirjallisuuteen. Tutkielman alussa on katsaus tämän hetkisestä kansainvälisestä liiketoimintaympäristöstä mukaan lukien tekoälyn mukanaan tuomat teknologia trendit. Tutkielman ensimmäisessä teoriaosioissa tarkastellaan myyntisuppiloa, joka on laajasti tunnettu työkaluna, joka tukee ja auttaa hahmottamaan asiakashankinta prosessia. Kokonaisvaltaisen ostopolun ymmärtämisen edistämiseksi myyntisuppiloa käsitellään yhdessä asiakaspolun kanssa. Asiakaspolkuanalyysi tuo asiakkaan näkökulmaa ostoprosessista, kun taas myyntisuppilo kuvaa yrityksen näkökulmaa. Yhdessä nämä kaksi teoreettistä viitekehystä kuvaavat asiakkaan matkaa aina ensimmäisestä kosketuspisteestä lopulliseen ostopäätökseen. Myyntisuppilon vaiheet esitellään tutkielmassa yksityiskohtaisesti, jotta voidaan osoittaa keskeiset suppilon vaiheet, missä tekoälyn käytöstä on potentiaalisesti hyötyä. Tutkielman tulokset osoittavat tekoälyn merkittävän roolin myynti- ja markkinointitehtävien tehostamisessa etenkin rutiininomaisissa, toistuvissa ja standarditehtävissä. Asiakashankinnan näkökulmasta merkittävimmät kohdat myyntisuppilossa ovat prospektointi sekä konversio. Tutkielman tulokset osoittavat tekoälyn mahdollisuudet etenkin liidien prospektoinnissa sekä konversiossa, sillä näissä vaiheissa tekoäly voi merkittävästi vähentää myyntiorganisaatioiden työkuormaa. Esimerkiksi. hyödyntämällä data-analyysia, koneoppimista ja personointia voidaan tehostaa liidien prospektointia ja sitä kautta parantaa myyntisuppiloa. Monet myyntitehtävät vaativat edelleen ihmisen älykkyyttä, minkä vuoksi tekoälyä käytetään usein täydentävänä työkaluna. Tutkielman tulokset havainnollistivat yritysten ja eri maiden välisten resurssierojen keskeisen vaikutuksen mahdollisuuksiin hyödyntää tekoälyä sekä siihen, minkälaisessa mittakaavassa tekoäly pystytään sisällyttämään yrityksen toimintaan. Yrityksen toimiessa kansainvälisesti tarve tehokkaalle myynnille- ja markkinoinnille korostuu, sillä mahdollisten asiakkaiden määrä kasvaa ja monipuolistuu, minkä vuoksi tarvitaan tehokas myyntisuppilo.
Keywords: Artificial Intelligence, Sales funnel, Management, Customer journey, Tekoäly, Myyntisuppilo, Hallinta, Ostopolku, Asiakaspolku